Analisis Strategi Pemasaran untuk Meningkatkan Penjualan Produk Ayam Goreng Menggunakan Metode SWOT dan AHP - Muhammad, Bima Andreawan; Isharyani, Muriani Emelda; Tosungku, La ode Ahmad Safar (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Warung Ayam Kalijaga, located in Bontang Utara, is facing declining sales due to an increase in competitors in the fast food industry, with current daily sales ranging from 10 to 15 chickens, compared to 20 to 25 in previous years. The promotional strategies rely heavily on word-of-mouth marketing, which is less effective for reaching a broader market. Therefore, it is necessary to design a marketing strategy based on SWOT analysis and the AHP method. The analysis results indicate an IFE Matrix score of 2.697 and an EFE Matrix score of 2.679, with the Warung positioned in quadrant V, recommending a